Electromagnetic synergistic wave-absorbing fiber reinforced resin matrix composite material, preparation method and application thereof
Patent Information
- Application Number
- CN202510782097.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-30
- Filing Date
- 2025-06-12
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-06-12
AI Technical Summary
[0006]鉴于上述的分析,本发明旨在提供一种电磁协同吸波纤维增强树脂基复合材料及其制备方法和应用,用以解决现有的结构型吸波复合材料存在的吸波材料分散均匀性差、生产效率低、吸收频宽较窄、吸波效果不佳等技术问题中至少一个
[0024]与现有技术相比,本发明至少可实现如下有益效果之一:
Smart Images

Figure CN120659305B_ABST
Abstract
Description
[0001] This invention patent application is based on the prior patent application filed on April 30, 2025, with application number 2025105598414 and invention title "An electromagnetic synergistic absorbing fiber reinforced resin matrix composite material and its preparation method and application". Technical Field
[0002] This invention relates to the field of microwave absorbing materials technology, and in particular to an electromagnetic synergistic microwave absorbing fiber-reinforced resin matrix composite material, its preparation method, and its application. Background Technology
[0003] Electromagnetic absorbing materials are functional materials that can effectively absorb incident electromagnetic wave energy and convert it into heat or other forms of energy through various loss mechanisms, thereby reducing electromagnetic interference. Carbon materials, due to their low density, large specific surface area, good stability, abundant defect sites, and excellent electrical conductivity and electrical modification properties, have become a research hotspot in the field of electromagnetic absorbing materials. However, carbon materials have a single mode of electromagnetic wave loss, high electrical modification can easily lead to impedance mismatch, and the absorption bandwidth is relatively narrow, making the achievement of broadband absorption still a challenge.
[0004] Based on their molding process and load-bearing capacity, microwave absorbing materials can be divided into two types: coating type and structural type. Microwave absorbing coatings involve dispersing conductive carbon-based materials in a polymer matrix or binder and directly coating them onto the surface of an object. While this method is simple to prepare, it suffers from drawbacks such as large overall mass, narrow effective absorption frequency band, and susceptibility to detachment. Structural microwave absorbing materials, on the other hand, are multifunctional composite materials that can simultaneously meet the requirements of microwave absorption and load-bearing capacity. They also possess excellent mechanical properties, thermal stability, and chemical stability, and offer high design flexibility, making them valuable for achieving integrated structure and function.
[0005] The common method for preparing structural microwave absorbing composite materials using existing technology involves using continuous fibers as reinforcement and incorporating microwave absorbing particles into a resin matrix. This method suffers from the problem of uneven dispersion of the microwave absorbing particles, which weakens the uniformity of the material's microwave absorption performance. Simultaneously, the increased viscosity of the polymer resin makes it difficult to apply manufacturing processes such as resin transfer molding and impregnation, ultimately resulting in low production efficiency and poor microwave absorption performance. Summary of the Invention
[0006] Based on the above analysis, the present invention aims to provide an electromagnetic synergistic absorbing fiber reinforced resin matrix composite material, its preparation method and application, to solve at least one of the technical problems of existing structural absorbing composite materials, such as poor uniformity of absorbing material dispersion, low production efficiency, narrow absorption bandwidth and poor absorbing effect.
[0007] An electromagnetic synergistic absorbing fiber-reinforced resin matrix composite material, comprising:
[0008] Electro-absorbing wave layer, magnetic wave-absorbing wave layer;
[0009] The electro-absorbing layer includes electro-modified fibers with an electro-coated modification layer on their outer periphery and a matrix resin filling the gaps between the electro-modified fibers;
[0010] The magnetic wave-absorbing layer includes magnetically modified fibers with a magnetically coated modified layer on their outer periphery and a matrix resin filling the gaps between the magnetically modified fibers;
[0011] The electro-absorbing wave layer and the magnetic absorbing wave layer are stacked sequentially.
[0012] Preferably, the electro-absorbing wave layer has 1 to 3 layers and the magnetic wave-absorbing layer has 1 to 3 layers; preferably, the electro-absorbing wave layer has 1 layer and the magnetic wave-absorbing layer has 1 layer.
[0013] Preferably, the incident surface of the electro-absorbing wave layer is provided with a magnetic wave-absorbing layer, and the incident electromagnetic wave enters the electro-absorbing wave layer after passing through at least one magnetic wave-absorbing layer.
[0014] Preferably, the electro-absorbing wave layer comprises multiple electro-modified fiber monolayers stacked together, and the magnetic wave-absorbing layer comprises multiple magnetically modified fiber monolayers stacked together.
[0015] Preferably, the number of modified fiber monolayers in the electro-absorbing wave layer is ≥5, and the number of modified fiber monolayers in the magnetic wave-absorbing layer is ≥5.
[0016] Preferably, the electrocoating modified layer includes an electromodified microwave absorbing agent and a necessary adhesive; the magnetic coating modified layer includes a magnetically modified microwave absorbing agent and a necessary adhesive.
[0017] Preferably, the electromodified microwave absorbing agent includes one or more of multi-walled carbon nanotubes, activated carbon, highly conductive carbon black, reduced graphene oxide, or vapor-grown carbon fibers.
[0018] Preferably, the magnetically modified microwave absorbing agent comprises a metal oxide composed of one or more of iron, cobalt, and nickel, or an alloy composed of two or more of iron, cobalt, and nickel.
[0019] A method for preparing an electromagnetically synergistically absorbing fiber-reinforced resin matrix composite material, comprising:
[0020] Electro-absorbing layer preforms were prepared using fiber monolayers modified with an electro-modified microwave absorbing agent.
[0021] A magnetic wave-absorbing layer preform was prepared using fiber monolayers modified with a magnetically modified wave-absorbing agent.
[0022] Electromagnetic synergistic absorbing fiber-reinforced resin matrix composite material is prepared by stacking preforms of electro-absorbing and magnetic absorbing layers.
[0023] An application of an electromagnetic synergistic absorbing fiber reinforced resin matrix composite material, wherein the electromagnetic synergistic absorbing fiber reinforced resin matrix composite material or the electromagnetic synergistic absorbing fiber reinforced resin matrix composite material prepared by the above method is used for electromagnetic radiation and interference protection in buildings, equipment, etc.
[0024] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0025] (1) The modified fiber prepared by the present invention with a coating modification layer on the outer periphery of the fiber has better process matching, is less prone to delamination, has strong design flexibility, has the advantage of integral molding, and has higher mechanical strength compared with the conventional method of laying the absorbing material on the fiber surface. Compared with the conventional technology of dissolving the absorbing material into the matrix resin and reinforcing fiber to construct a relatively uniform absorbing material, the present invention forms a regular and orderly absorbing area by coating the outer periphery of the fiber with a coating modification layer, and at the same time forms a regular and orderly refraction and reflection area in the gap between the fibers. Due to the different materials, the absorbing area and the refraction and reflection area form an interface with different absorption rates, which helps to improve the absorption effect, increase the absorption rate and absorption bandwidth.
[0026] (2) This invention improves the problem of poor dispersion uniformity of the absorbing material in non-polar resin by dissolving the absorbing material in a polar solvent to prepare a slurry and coating it on the outer surface of the fiber. At the same time, it avoids the defects of the increased viscosity of the polymer resin, which makes it difficult to apply the resin transfer molding, impregnation and other manufacturing processes, thus improving production efficiency and absorbing effect.
[0027] (3) By setting a magnetic wave-absorbing layer on the incident surface of the electro-absorbing layer, the present invention improves the impedance matching of the composite material, so that electromagnetic waves can enter the interior of the material as much as possible, thereby improving the electromagnetic wave absorption rate.
[0028] (4) The present invention helps to form regular and orderly refraction and reflection zones and wave absorption zones by stacking multiple modified fiber monolayers in the electro-absorbing layer and the magnetic absorbing layer and filling the spaces between each modified fiber monolayer with matrix resin. The different materials between the refraction and reflection zones form interfaces with different absorption rates, which helps to improve the absorption effect, increase the absorption rate and the effective absorption bandwidth.
[0029] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description
[0030] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0031] Figure 1a A schematic diagram of the composite material structure prepared in Example 1;
[0032] Figure 1b This is a schematic diagram of the composite material structure prepared in Example 2;
[0033] Figure 1c This is a schematic diagram of the composite material structure prepared in Example 3;
[0034] Figure 1d This is a schematic diagram of the composite material structure prepared in Example 4;
[0035] Figure 2 The graphs show the reflectance test results of the composite materials in Examples 1-4;
[0036] Figure 3 The graphs show the reflection loss of the composite materials in Example 3 and Comparative Examples 1-2 as a function of frequency.
[0037] Figure Labels
[0038] 001 - Electro-absorbing wave layer; 002 - Magnetic-absorbing wave layer. Detailed Implementation
[0039] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0040] Terminology Definition
[0041] In this invention, "up and down" refers to the direction of electromagnetic wave incident on the composite material as "up," and "stacked from top to bottom" means stacked sequentially according to the direction of electromagnetic wave incident.
[0042] In a first aspect, the present invention provides an electromagnetic synergistic absorbing fiber reinforced resin matrix composite material, comprising: an electro-absorbing layer and a magnetic absorbing layer;
[0043] The electro-absorbing layer includes electro-modified fibers with an electro-coated modification layer on their outer periphery and a matrix resin filling the gaps between the electro-modified fibers;
[0044] The magnetic wave-absorbing layer includes magnetically modified fibers with a magnetically coated modified layer on their outer periphery and a matrix resin filling the gaps between the magnetically modified fibers;
[0045] The electro-absorbing wave layer and the magnetic absorbing wave layer are stacked sequentially.
[0046] In practice, the layered arrangement of the electro-absorbing layer and the magnetic absorbing layer creates multiple interfaces with different electromagnetic parameters within the material, forming multiple interface polarizations. This also causes electromagnetic wave reflection, increasing the dissipation path of electromagnetic waves within the absorbing body, thereby enhancing the absorption of electromagnetic waves. Simultaneously, the invention forms a regular and ordered absorbing region by coating the outer periphery of the fiber with a modified layer, while regular and ordered refractive and reflective regions are formed in the gaps between the fibers. The absorbing region and the refractive and reflective regions form interfaces with different absorption rates due to the different materials, which helps to improve the absorption effect, increase the absorption rate, and improve the absorption bandwidth.
[0047] Compared with existing technologies, the modified fibers prepared by this invention, with a coating modification layer on the outer periphery of the fibers, have better process matching during preparation than conventional methods of laying absorbing materials on the fiber surface. They are less prone to delamination, have strong design flexibility, and have the advantage of integral molding, as well as higher mechanical strength. Compared with conventional technologies that dissolve the absorbing material in the matrix resin and reinforcing fibers to construct a relatively uniform absorbing material, this invention forms a regular and orderly absorbing zone by coating the outer periphery of the fibers with a coating modification layer. At the same time, regular and orderly refractive and reflective zones are formed in the gaps between the fibers. Due to the different materials, the absorbing zone and the refractive and reflective zone form an interface with different absorption rates, which helps to improve the absorption effect, increase the absorption rate and absorption bandwidth, and improve the problems of poor dispersion uniformity and low production efficiency of absorbing materials.
[0048] Preferably, the electro-absorbing layer has 1 to 3 layers, and the magnetic absorbing layer has 1 to 3 layers;
[0049] More preferably, the electro-absorbing wave layer has one layer and the magnetic wave-absorbing layer has one layer.
[0050] It should be noted that the multi-layer structure with alternating electric and magnetic wave-absorbing layers can create multiple interfaces with different electromagnetic parameters within the material, forming multiple interface polarizations. It can also cause multiple reflections of electromagnetic waves, increasing the dissipation path of electromagnetic waves within the absorber, thereby enhancing the absorption of electromagnetic waves. However, the number of electric and magnetic wave-absorbing layers is not necessarily better the more there are. A good effect is achieved when there is one electric wave-absorbing layer and one magnetic wave-absorbing layer.
[0051] Specifically, the thickness of the electro-absorbing layer is 2mm to 5mm, and can be 2mm, 2.5mm, 2.8mm, 3mm, 3.2mm, 3.4mm, 3.6mm, 4.0mm, 4.2mm, 4.4mm, 4.6mm, 4.8mm, or 5.0mm; the thickness of the magnetic absorbing layer is 1mm to 5mm, and can be 1mm, 1.5mm, 1.8mm, 2mm, 2.5mm, 2.8mm, 3mm, 3.2mm, 3.4mm, 3.6mm, 4.0mm, 4.2mm, 4.4mm, 4.6mm, 4.8mm, or 5.0mm.
[0052] Preferably, the incident surface of the electro-absorbing wave layer is provided with a magnetic wave-absorbing layer, and the incident electromagnetic wave enters the electro-absorbing wave layer after passing through at least one magnetic wave-absorbing layer.
[0053] It should be noted that the incident surface of the electro-absorbing layer is equipped with a magnetic absorbing layer, which can effectively improve the impedance matching of the material and allow electromagnetic waves to enter the interior of the material as much as possible.
[0054] Compared with the prior art, the present invention improves the impedance matching of the composite material by setting a magnetic wave-absorbing layer on the incident surface of the electro-absorbing layer, so that electromagnetic waves can enter the interior of the material as much as possible, thereby improving the electromagnetic wave absorption rate.
[0055] Preferably, the electro-absorbing wave layer comprises multiple electro-modified fiber monolayers stacked together, and the magnetic wave-absorbing layer comprises multiple magnetically modified fiber monolayers stacked together.
[0056] It should be noted that the applicant's research found that filling the spaces between the modified fiber monolayers with matrix resin and increasing the number of modified fiber monolayers in the electro-absorbing and magnetic absorbing layers can improve the absolute value of the minimum reflection loss and the effective absorption bandwidth. This is because, similar to filling the gaps between fibers with matrix resin, the stacking of multiple modified fiber monolayers and the filling of the spaces between each modified fiber monolayer with matrix resin both help to form regular and ordered refractive and reflective regions, as well as absorption regions. Furthermore, the different materials between the refractive and reflective regions create interfaces with different absorption rates, which helps to improve the absorption effect, increase the absorption rate, and enhance the effective absorption bandwidth.
[0057] Compared with the prior art, the present invention, by stacking multiple modified fiber monolayers in the electro-absorbing layer and the magnetic absorbing layer and filling the spaces between each modified fiber monolayer with matrix resin, helps to form regular and orderly refraction and reflection zones and wave absorption zones. Furthermore, the different materials between the refraction and reflection zones form interfaces with different absorption rates, which helps to improve the absorption effect, increase the absorption rate and the effective absorption bandwidth.
[0058] Preferably, the number of modified fiber monolayers in the electro-absorbing wave layer and the magnetic absorbing wave layer is ≥5.
[0059] More preferably, the number of modified fiber monolayers in the electro-absorbing wave layer and the magnetic absorbing wave layer is ≥10.
[0060] Specifically, the modified fiber monolayer can be in the form of fiber cloth or fiber web; the fiber web surface density is 0.40 g / cm³. 2 ~0.85g / cm 2 It can be 0.40 g / cm³. 2 0.42g / cm 2 0.43g / cm 2 0.46 g / cm 2 0.48g / cm 2 0.50g / cm2 0.52g / cm 2 0.55g / cm 2 0.56g / cm 2 0.58g / cm 2 0.60 g / cm 2 0.64 g / cm 2 0.66 g / cm 2 0.68g / cm 2 0.70g / cm 2 0.74g / cm 2 0.76 g / cm 2 0.78g / cm 2 0.80g / cm 2 or 0.84 g / cm 2 .
[0061] The surface density of the fiber fabric is 0.9 g / cm³. 2 ~1.5g / cm 2 It can be 0.9g / cm³. 2 1.0g / cm 2 1.1g / cm 2 1.2g / cm 2 1.3g / cm 2 1.4g / cm 2 Or 1.5g / cm 2 .
[0062] Preferably, the density of the fiber web tread is 0.50 g / cm³. 2 ~0.70g / cm 2 The surface density of the fiber fabric is 0.9 g / cm³. 2 ~1.2g / cm 2 .
[0063] It should be noted that if the areal density is too high, the gaps between fibers will be reduced, which will decrease the reflection and absorption of electromagnetic waves within the material; if the areal density is too low, it will be difficult to meet the strength requirements.
[0064] Specifically, the thickness of the modified fiber monolayer in the electro-absorbing layer and the magnetic absorbing layer ranges from 0.2 mm to 0.5 mm, and can be 0.2 mm, 0.3 mm, 0.4 mm, or 0.5 mm; the coating slurry amount of the modified fiber monolayer is 400 g / m². 2 ~900g / m 2 It can be 400g / m 2 420g / m 2 480g / m 2 500g / m 2 510g / m 2560g / m 2 580g / m 2 600g / m 2 620g / m 2 640g / m 2 660g / m 2 680g / m 2 700g / m 2 720g / m 2 740g / m 2 790g / m 2 800g / m 2 820g / m 2 840g / m 2 860g / m 2 880g / m 2 Or 900g / m 2 .
[0065] Preferably, the fiber layers are connected by knitting, the knitting material is quartz fiber, and the knitting density is 10 stitches / cm. 2 ~20 stitches / cm 2 It can provide sufficient connection strength for each fiber layer.
[0066] The diameter of the original fibers in the modified fibers ranges from 5μm to 10μm, and can be 5μm, 6μm, 7μm, 8μm, 9μm or 10μm.
[0067] It should be noted that when the amount of slurry coated on a single modified fiber is within the above range, it helps to match the areal density and form appropriately sized, regular and orderly refractive and reflective zones between the fibers, which helps to improve the absorption effect, increase the absorption rate and absorption bandwidth.
[0068] Specifically, the electro-coating modified layer includes an electro-modified microwave absorbing agent and necessary adhesives; the magnetic coating modified layer includes a magnetically modified microwave absorbing agent and necessary adhesives.
[0069] Specifically, the electromodified microwave absorber includes one or more of the following: multi-walled carbon nanotubes (MWCNT), activated carbon (CB), highly conductive carbon black (Super P), reduced graphene oxide (RGO), or vapor-grown carbon fiber (VGCF).
[0070] Preferably, the electromodified microwave absorber is a multi-walled carbon nanotube (MWCNT), reduced graphene oxide (RGO), or a mixture of multi-walled carbon nanotube (MWCNT) and vapor-grown carbon fiber (VGCF).
[0071] More preferably, the electromodified microwave absorber is a mixture of multi-walled carbon nanotubes (MWCNTs) and reduced graphene oxide (RGO).
[0072] Specifically, the mass ratio of the mixture of multi-walled carbon nanotubes (MWCNTs) and reduced graphene oxide (RGO) is 0.8 to 1.2:1, and can be 0.8:1, 0.82:1, 0.84:1, 0.85:1, 0.88:1, 0.9:1, 0.92:1, 0.94:1, 0.95:1, 0.96:1, 0.98:1, 1:1, 1.04:1, 1.05:1, 1.06:1, 1.08:1, 1.10:1, 1.12:1, 1.14:1, 1.15:1, 1.18:1, or 1.20:1.
[0073] Preferably, the mass ratio of the mixture of multi-walled carbon nanotubes (MWCNTs) and reduced graphene oxide (RGO) is 1:1.
[0074] Specifically, magnetically modified microwave absorbers include metal oxides composed of one or more of iron, cobalt, and nickel, or alloys composed of two or more of iron, cobalt, and nickel.
[0075] Specifically, the average particle size of the magnetically modified microwave absorbing agent is 1μm to 10μm, and can be 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm; the average particle size of the electrically modified microwave absorbing agent is 20nm to 100μm (irregularly shaped particles, the particle size is taken as the diameter of its circumscribed sphere).
[0076] Preferably, the average particle size of the magnetically modified microwave absorbing agent is 3μm to 5μm; the average particle size of the electrically modified microwave absorbing agent is 50nm to 50μm.
[0077] Specifically, both the magnetically modified and electrically modified microwave absorbers have particle sizes within the aforementioned range, are uniformly dispersed, and are not prone to agglomeration.
[0078] The adhesive includes one or more of polyacrylonitrile or methyl methacrylate.
[0079] The fibers include one or more of quartz fibers, silicon carbide fibers, glass fibers, or high-silica fibers.
[0080] Specifically, the electro-modified microwave absorbing agent in the electro-absorbing layer has a mass percentage of 1% to 8%, the fiber mass percentage is 20% to 30%, and the remainder is matrix resin.
[0081] Specifically, the magnetically modified microwave absorbing agent in the magnetic absorbing layer has a mass percentage of 20-50%, the fiber mass percentage is 20%-30%, and the remainder is matrix resin.
[0082] Preferably, the thickness ratio of the electro-absorbing wave layer to the magnetically absorbing wave layer is (1-2):1.5.
[0083] It should be noted that the electro-absorbing layer and the magnetic absorbing layer improve the impedance matching of the composite material within this thickness range, allowing electromagnetic waves to enter the interior of the material as much as possible, thereby improving the electromagnetic wave absorption rate and absorption bandwidth.
[0084] Specifically, the composite material has a thickness of 2mm to 10mm and a density of 0.7kg / m³. 3 ~1.5kg / m 3 .
[0085] A preferred embodiment is a two-layer magnetic-modified fiber composite material with an electric-modified fiber layer on top and an electric-modified fiber layer on the bottom. The fiber stacking order from top to bottom is ≥10 magnetically modified fiber monoliths and ≥10 electric-modified fiber monoliths. The minimum reflection loss of the fiber composite material is ≤-36dB and the effective absorption bandwidth is ≥12GHz.
[0086] On the other hand, the present invention provides a method for preparing an electromagnetically synergistic absorbing fiber-reinforced resin-based composite material, comprising:
[0087] Electro-absorbing layer preforms were prepared using fiber monolayers modified with an electro-modified microwave absorbing agent.
[0088] A magnetic wave-absorbing layer preform was prepared using fiber monolayers modified with a magnetically modified wave-absorbing agent.
[0089] Electromagnetic synergistic absorbing fiber-reinforced resin matrix composite material is prepared by stacking preforms of electro-absorbing and magnetic absorbing layers.
[0090] Specifically, the preparation method of the electromagnetic synergistic absorbing fiber reinforced resin matrix composite material includes:
[0091] S1: Weigh out appropriate amounts of electro-modified / magnetically modified microwave absorbing agent and binder according to the proportion, and mix them thoroughly with solvent to form electro-modified microwave absorbing slurry and magnetically modified microwave absorbing slurry;
[0092] S2: Electro-modified microwave absorbing paste is coated onto fiber monosheets by spraying or brushing, and then dried to obtain electro-modified fiber monosheets; magnetically modified microwave absorbing paste is coated onto fiber monosheets, and then dried to obtain magnetically modified fiber monosheets.
[0093] S3: Arrange and stack the electrically modified fiber monolayers and magnetically modified fiber monolayers from S2, and inject matrix resin to prepare electromagnetic synergistic absorbing fiber reinforced resin matrix composite material.
[0094] During implementation, step S3 includes:
[0095] S301: Vertical fiber monolithic sheet is sewn together with multiple fiber monolithic sheets to form a fiber preform;
[0096] S302: The fiber preform is laid in the mold, the matrix resin is injected into the mold under pressure, and the mixture is cured and dried in a high-temperature environment to obtain the electromagnetic synergistic absorbing fiber reinforced resin matrix composite material.
[0097] During implementation, in step S1, the mass ratio of the electrically modified microwave absorbing agent to the binder in the electrically modified microwave absorbing slurry is (4-20):1; the mass ratio of the magnetically modified microwave absorbing agent to the binder in the magnetically modified microwave absorbing slurry is (30-50):1; and the amount of solvent used relative to the solid component in both the electrically modified and magnetically modified microwave absorbing slurries is 300ml / kg to 500ml / kg.
[0098] Compared with the prior art, the present invention improves the problem of poor dispersion uniformity of microwave absorbing materials in non-polar resins by dissolving the microwave absorbing material in a polar solvent to prepare a slurry and coating it on the outer surface of the fiber. At the same time, it avoids the defects of the increased viscosity of polymer resin, which makes it difficult to apply manufacturing processes such as resin transfer molding and impregnation, thereby improving production efficiency and microwave absorption effect.
[0099] The adhesive includes one or more of polyacrylonitrile or methyl methacrylate.
[0100] It should be noted that the mass ratio of electro-modified microwave absorber to binder, the mass ratio of magnetically modified microwave absorber to binder, and the relative amount of solvent to solid component in electro-modified microwave absorber slurry and magnetically modified microwave absorber slurry within the above ranges help to form regularly ordered refractive and reflective zones of appropriate size in the gaps between fibers, which helps to improve the absorption effect, absorption rate and absorption bandwidth.
[0101] The solvent includes one of N,N-dimethylformamide, N-methylpyrrolidone, or N-ethylpyrrolidone.
[0102] Furthermore, depending on the thickness and performance requirements of the composite material, the fiber preform in step S3 can be composed of 8 to 40 fibers loaded with the same or different types and contents of electrically modified / magnetically modified microwave absorbing agents.
[0103] Furthermore, in step S3, the curing temperature and time in the high-temperature environment are 60℃~100℃ and 12h~48h, respectively.
[0104] Thirdly, an application of the electromagnetic synergistic absorbing fiber-reinforced resin matrix composite material as described above, which is applied in the field of electromagnetic wave absorption, specifically for protection against electromagnetic radiation and interference in buildings, equipment, etc.
[0105] To better illustrate the present invention, the following embodiments and comparative examples are provided:
[0106] Example 1
[0107] This embodiment discloses a two-layer electromagnetic wave absorbing composite material with electric and magnetic properties and its preparation method. The specific preparation steps are as follows:
[0108] S1: Weigh 1g of methyl methacrylate and add it to 400ml of N,N-dimethylformamide. Stir thoroughly at room temperature until dissolved. Weigh 2.5g of a mixture of multi-walled carbon nanotubes (MWCNTs) and reduced graphene oxide (RGO) in a 1:1 mass ratio and add it to the above solution in portions. Sonicate for 10-15 minutes to disperse evenly, and stir thoroughly until a suspension is formed to obtain the electrically modified microwave absorbing slurry. Separately, weigh 3g of methyl methacrylate and add it to 400ml of N,N-dimethylformamide. Stir thoroughly at room temperature until dissolved. Weigh 120g of carbonyl iron powder and add it to the above solution. Stir mechanically until a suspension is formed to obtain the magnetically modified microwave absorbing slurry. The average particle size of the magnetically modified microwave absorbing agent is 3μm; the average particle size of the electrically modified microwave absorbing agent is 100nm.
[0109] S2: Weigh 25g of the above slurry each time, and evenly disperse it onto a single quartz fiber mesh using a spraying process. Then, place the fibers in an 80℃ oven and dry for 10 hours to obtain electrically modified quartz fibers and magnetically modified quartz fibers. The average diameter of the original fibers in the modified fibers is 10μm, and the surface density of a single quartz fiber is 0.27g / cm³. 3 The modified fiber monolayer in the electro-absorbing layer has a thickness of 0.2 mm, and the coating slurry amount of the modified fiber monolayer is 500 g / m². 2 The modified fiber monolayer in the magnetic wave absorption layer has a thickness of 0.3 mm, and the coating slurry amount of the modified fiber monolayer is 600 g / m². 2 .
[0110] S3: Take 10 electro-modified quartz fiber monolayers and 10 magnetically modified quartz fiber monolayers, and stack them in the following order: the electro-modified quartz fiber monolayers form an electro-absorbing layer 001 on top, and the magnetically modified quartz fiber monolayers form a magnetically absorbing layer 002 on the bottom. The thickness of the electro-absorbing layer is 2mm; the thickness of the magnetically absorbing layer is 3mm. Figure 1a As shown. The fibers are joined together using a stitching process to form a fiber preform. The fiber preform is laid in a 330mm × 330mm × 5mm mold, and silicone resin is injected under pressure until the fiber preform is completely impregnated with the silicone resin solution, after which the mold is sealed. The mold after injection is placed in an 80℃ oven for curing for 24 hours, and then dried at 100℃ for 24 hours.
[0111] The electro-modified microwave absorbing agent in the electro-absorbing layer accounts for 2% of the mass, the fiber accounts for 20% of the mass, and the remainder is silicone resin.
[0112] The magnetic wave-absorbing layer contains 25% magnetically modified wave-absorbing agent by mass, 30% fiber by mass, and the remainder is silicone resin.
[0113] The thickness ratio of the electro-absorbing wave layer to the magnetically absorbing wave layer is 1:1.5.
[0114] The tensile and compressive properties of the electromagnetic synergistic absorbing fiber reinforced resin matrix composite material prepared in this embodiment were tested according to GB / T 1447-2005 and GB / T 1448-2005. The loading speed for each experiment was 2 mm / min, and 5 samples were tested in parallel in each group. The maximum tensile stress of the composite material was 18.6 MPa and the compressive stress was 25.4 MPa, which showed good mechanical properties.
[0115] The complex conductivity constant and complex permeability of the electromagnetic synergistic absorbing fiber reinforced resin matrix composite material prepared in this embodiment were tested in the range of 2GHz to 18GHz using the free space method according to GB / T 42741-2023. The material was cut into 300mm×300mm×5mm flat plates. According to the transmission line theory, the reflection loss of the absorbing composite material at different thicknesses can be calculated using formulas (1) and (2).
[0116] Formula (1): In the formula, Z is the self-used space impedance, which is approximately 377Ω. in This is the input impedance.
[0117] Formula (2): In the formula ε r μ is the complex conductivity constant. r denoted as complex permeability, j represents the imaginary part, f is the frequency, d is the sample thickness, and c is the speed of light.
[0118] According to calculations, the minimum reflection loss of the material as a function of frequency is -17.9dB, and the effective absorption bandwidth is 5.1GHz.
[0119] Example 2
[0120] This embodiment discloses a four-layer electrically conductive wave-absorbing composite material and its preparation. The specific preparation steps are as follows:
[0121] The difference from Example 1 is that in step S3, the fiber stacking order from top to bottom is 5 electro-modified quartz fiber monolayers, 5 magnetically modified quartz fiber monolayers, 5 electro-modified quartz fiber monolayers, and 5 magnetically modified quartz fiber monolayers, as shown below. Figure 1b As shown, an electrically modified quartz fiber monolayer forms an electrically absorbing wave layer 001, and a magnetically modified quartz fiber monolayer forms a magnetically absorbing wave layer 002.
[0122] According to the test (test method is the same as in Example 1), the minimum reflection loss of the electromagnetic synergistic absorbing fiber reinforced resin matrix composite material prepared in this example is -15.8dB, and the effective absorption bandwidth is 4.9GHz.
[0123] Example 3
[0124] This embodiment discloses a two-layer magnetic upper and electric lower wave-absorbing composite material and its preparation. The specific preparation steps are as follows:
[0125] The difference from Example 1 is that in step S3, the fiber stacking order from top to bottom is 10 magnetically modified quartz fiber monolayers and 10 electrically modified quartz fiber monolayers, as shown below. Figure 1c As shown, an electrically modified quartz fiber monolayer forms an electrically absorbing wave layer 001, and a magnetically modified quartz fiber monolayer forms a magnetically absorbing wave layer 002.
[0126] According to the test (test method is the same as in Example 1), the minimum reflection loss of the electromagnetic synergistic absorbing fiber reinforced resin matrix composite material prepared in this example is -36.3dB, and the effective absorption bandwidth is 12.3GHz.
[0127] Example 4
[0128] This embodiment discloses a four-layer magnetic-on-top and electrically-on-bottom wave-absorbing composite material and its preparation. The specific preparation steps are as follows:
[0129] The difference from Example 1 is that in step S3, the stacking order of the fibers from top to bottom is 5 magnetically modified quartz fiber monolayers, 5 electro-modified quartz fiber monolayers, 5 magnetically modified quartz fiber monolayers, and 5 electro-modified quartz fiber monolayers, as shown below. Figure 1d As shown, an electrically modified quartz fiber monolayer forms an electrically absorbing wave layer 001, and a magnetically modified quartz fiber monolayer forms a magnetically absorbing wave layer 002.
[0130] According to the test (test method is the same as in Example 1), the minimum reflection loss of the electromagnetic synergistic absorbing fiber reinforced resin matrix composite material prepared in this example is -22.4dB, and the effective absorption bandwidth is 7.4GHz.
[0131] Example 5
[0132] The difference from Example 1 is that the electromodified microwave absorber is a multi-walled carbon nanotube.
[0133] The specific preparation steps for the microwave absorbing composite material are as follows:
[0134] (1) Weigh 1g of methyl methacrylate and add it to 400ml of N,N-dimethylformamide. Stir thoroughly at room temperature to dissolve it. Weigh 3g of multi-walled carbon nanotubes and add them to the above solution in portions. Sonicate for 10-15min to disperse them evenly, and stir thoroughly until a suspension is formed to obtain the electrically modified microwave absorbing slurry. Separately weigh 3g of methyl methacrylate and add it to 400ml of N,N-dimethylformamide. Stir thoroughly at room temperature to dissolve it. Weigh 120g of carbonyl iron powder and add it to the above solution. Stir mechanically until a suspension is formed to obtain the magnetically modified microwave absorbing slurry. The average particle size of the magnetically modified microwave absorbing agent is 3μm; the average particle size of the electrically modified microwave absorbing agent is 20μm.
[0135] (2) Weigh 25g of the above slurry each time, and evenly disperse it onto a single quartz fiber mesh using a spraying process. Then, place the fibers in an 80℃ oven and dry for 10 hours to obtain electrically modified quartz fiber monolayers and magnetically modified quartz fiber monolayers. The diameter of the original fibers in the modified fibers ranges from 5 to 10 μm; the areal density of the quartz fiber monolayers is 0.65 g / cm³. 2 The modified fiber monolayer in the electro-absorbing layer has a thickness of 0.2 mm, and the coating slurry amount of the modified fiber monolayer is 550 g / m². 2 .
[0136] (3) Take 10 electro-modified quartz fiber monolayers and 10 magnetically modified quartz fiber monolayers, and stack them in the order of forming an electro-absorbing layer on top and a magnetically modified quartz fiber monolayer on the bottom, as shown in Figure 1. The thickness of the electro-absorbing layer is 2 mm; the thickness of the magnetically modified layer is 3 mm. Connect them into a fiber preform by stitching. Lay the fiber preform in a 330 mm × 330 mm × 5 mm mold, pressurize and inject silicone resin until the fiber preform is completely impregnated with the silicone resin solution, and then seal the mold. Place the mold after injection in an 80 °C oven to cure for 24 h, and then dry it in a 100 °C environment for 24 h. The mass percentage of the electro-modified absorbing agent in the electro-absorbing layer is 1.5%, the mass percentage of the fiber is 20%, and the remainder is silicone resin.
[0137] The magnetic wave-absorbing layer contains 26% magnetically modified wave-absorbing agent by mass, 30% fiber by mass, and the remainder is silicone resin.
[0138] The thickness ratio of the electro-absorbing wave layer to the magnetically absorbing wave layer is 1.2:1.5.
[0139] According to the test (test method is the same as in Example 1), the electromagnetic synergistic absorbing fiber reinforced resin matrix composite material prepared in this example has a minimum reflection loss of -19.2dB and an effective absorption bandwidth of 5.7GHz.
[0140] Example 6
[0141] The difference from Example 1 is that the electromodified microwave absorbing agent is reduced graphene oxide.
[0142] The specific preparation steps for the microwave absorbing composite material are as follows:
[0143] (1) Weigh 1g of methyl methacrylate and add it to 400ml of N,N-dimethylformamide. Stir thoroughly at room temperature until dissolved. Weigh 2g of reduced graphene oxide and add it to the above solution in portions. Sonicate for 10-15min to disperse it evenly, and stir thoroughly until a suspension is formed to obtain the electrically modified microwave absorbing slurry. Separately weigh 3g of methyl methacrylate and add it to 400ml of N,N-dimethylformamide. Stir thoroughly at room temperature until dissolved. Weigh 120g of carbonyl iron powder and add it to the above solution. Stir mechanically until a suspension is formed to obtain the magnetically modified microwave absorbing slurry. The average particle size of the magnetically modified microwave absorbing agent is 3μm; the average particle size of the electrically modified microwave absorbing agent is 5μm.
[0144] (2) Weigh 25g of the above slurry each time, and evenly disperse it onto a single quartz fiber mesh using a spraying process. Then, place the fibers in an 80℃ oven and dry for 10 hours to obtain electrically modified quartz fiber monolayers and magnetically modified quartz fiber monolayers. The diameter of the original fibers in the modified fibers ranges from 5 to 10 μm; the areal density of the quartz fiber monolayers is 0.26 g / cm³. 2 The modified fiber monolayer in the electro-absorbing layer has a thickness of 0.2 mm, and the coating slurry amount of the modified fiber monolayer is 600 g / m². 2 .
[0145] (3) Take 10 electro-modified quartz fiber monolayers and 10 magnetically modified quartz fiber monolayers, and stack them in the order of forming an electro-absorbing layer on top and a magnetically modified quartz fiber monolayer on the bottom, as shown in Figure 1. The thickness of the electro-absorbing layer is 2 mm; the thickness of the magnetically modified layer is 3 mm. Connect them into a fiber preform by stitching. Lay the fiber preform in a 330 mm × 330 mm × 5 mm mold, pressurize and inject silicone resin until the fiber preform is completely impregnated with the silicone resin solution, and then seal the mold. Place the mold after injection in an 80 °C oven to cure for 24 h, and then dry it in a 100 °C environment for 24 h. The mass percentage of the electro-modified absorbing agent in the electro-absorbing layer is 2.1%, the mass percentage of the fiber is 20%, and the remainder is silicone resin.
[0146] The magnetic wave-absorbing layer contains 25% magnetically modified wave-absorbing agent by mass, 30% fiber by mass, and the remainder is silicone resin.
[0147] The thickness ratio of the electro-absorbing wave layer to the magnetically absorbing wave layer is 1:1.5.
[0148] According to the test (test method is the same as in Example 1), the electromagnetic synergistic absorbing fiber reinforced resin matrix composite material prepared in this example has a minimum reflection loss of -17.5dB and an effective absorption bandwidth of 7.2GHz.
[0149] Example 7
[0150] The difference from Example 1 is that the electromodified microwave absorbing agent is vapor-grown carbon fiber.
[0151] The specific preparation steps for the microwave absorbing composite material are as follows:
[0152] (1) Weigh 1g of methyl methacrylate and add it to 400ml of N,N-dimethylformamide. Stir thoroughly at room temperature until dissolved. Weigh 2.5g of vapor-grown carbon fiber and add it to the above solution in portions. Sonicate for 10-15min to disperse it evenly, and stir thoroughly until a suspension is formed to obtain the electrically modified microwave absorbing slurry. Separately weigh 3g of methyl methacrylate and add it to 400ml of N,N-dimethylformamide. Stir thoroughly at room temperature until dissolved. Weigh 120g of carbonyl iron powder and add it to the above solution. Stir mechanically until a suspension is formed to obtain the magnetically modified microwave absorbing slurry. The average particle size of the magnetically modified microwave absorbing agent is 3μm; the average particle size of the electrically modified microwave absorbing agent is 25μm.
[0153] (2) Weigh 25g of the above slurry each time, and evenly disperse it onto a single quartz fiber mesh using a spraying process. Then, place the fibers in an 80℃ oven and dry for 10 hours to obtain electrically modified quartz fiber monolayers and magnetically modified quartz fiber monolayers. The diameter of the original fibers in the modified fibers ranges from 5 to 10 μm; the crosslinking density of the quartz fiber monolayers is 0.75 g / cm³. 2 The modified fiber monolayer in the electro-absorbing layer has a thickness of 0.2 mm, and the coating slurry amount of the modified fiber monolayer is 600 g / m². 2 .
[0154] (3) Take 10 electro-modified quartz fiber monolayers and 10 magnetically modified quartz fiber monolayers, and stack them in the order of forming an electro-absorbing layer on top and a magnetically modified quartz fiber monolayer on the bottom, as shown in Figure 1. The thickness of the electro-absorbing layer is 2 mm; the thickness of the magnetically modified layer is 3 mm. Connect them into a fiber preform by stitching. Lay the fiber preform in a 330 mm × 330 mm × 5 mm mold, pressurize and inject silicone resin until the fiber preform is completely impregnated with the silicone resin solution, and then seal the mold. Place the mold after injection in an 80 °C oven to cure for 24 h, and then dry it in a 100 °C environment for 24 h. The mass percentage of the electro-modified absorbing agent in the electro-absorbing layer is 1.8%, the mass percentage of the fiber is 20%, and the remainder is silicone resin.
[0155] The magnetic wave-absorbing layer contains 24.3% magnetically modified wave-absorbing agent by mass, 30% fiber by mass, and the remainder is silicone resin.
[0156] The thickness ratio of the electro-absorbing wave layer to the magnetically absorbing wave layer is 1:1.5.
[0157] According to the test (test method is the same as in Example 1), the maximum tensile stress of the electromagnetic synergistic absorbing fiber-reinforced resin matrix composite material prepared in this example is 11.6 MPa. The minimum reflection loss is -16.7 dB, and the effective absorption bandwidth is 7.4 GHz.
[0158] Comparative Example 1
[0159] This comparative example discloses a C2 electrically modified microwave absorbing composite material and its preparation method. The specific preparation steps are as follows:
[0160] S1: Prepare only the electrically modified microwave absorbing slurry according to step S1 of Example 1;
[0161] S2: Prepare electromodified quartz fibers only according to step S2 of Example 1;
[0162] S3: Take 20 individually stacked electro-modified quartz fibers and connect them into a fiber preform using a stitching process. Lay the fiber preform in a 330mm×330mm×5mm mold and prepare an electro-modified microwave absorbing composite material using the same process;
[0163] The remaining conditions are the same as in Example 1.
[0164] The electromagnetic parameters were tested according to the test method of Example 1, and the results are shown in Table 1 below. Figure 3 .
[0165] Comparative Example 2
[0166] This comparative example discloses Fe4O magnetically modified microwave absorbing composite material and its preparation method. The specific preparation steps are as follows:
[0167] S1: Prepare the magnetically modified absorbing slurry according to step S1 of Example 1;
[0168] S2: Prepare magnetically modified quartz fibers only according to step S2 of Example 1;
[0169] S3: Take 20 pieces of magnetically modified quartz fiber and stack them sequentially. Then, connect them into a fiber preform by stitching. Lay the fiber preform in a 330mm×330mm×5mm mold and prepare the magnetically modified microwave absorbing composite material using the same process.
[0170] The remaining conditions are the same as in Example 1.
[0171] The electromagnetic parameters were tested according to the test method of Example 1, and the results are shown in Table 1 below. Figure 3 .
[0172] Compared with Examples 1-4, the main difference lies in the different positions and arrangements of the electrically modified functional layer and the magnetic functional layer in the electromagnetic synergistic absorbing fiber reinforced resin matrix composite material. By adjusting the position and arrangement of the electrically modified functional layer and the magnetic functional layer, the overall impedance matching of the material and the distribution of electric and magnetic fields in the material can be adjusted, thereby enhancing the absorption of electromagnetic waves.
[0173] Compared with Examples 1-4, by setting a magnetic wave-absorbing layer on the incident surface of the electro-absorbing layer, the impedance matching of the composite material is improved, allowing electromagnetic waves to enter the interior of the material as much as possible, thereby improving the electromagnetic wave absorption rate. Increasing the number of modified fiber monolayers in the electro-absorbing and magnetic wave-absorbing layers can improve the absolute value of the minimum reflection loss and the effective absorption bandwidth.
[0174] As shown in Examples 1-7, the composite material prepared by the present invention is composed of alternating layers of electro-absorbing and magnetically absorbing layers. The number of electro-absorbing and magnetically absorbing layers is 1 to 2, the thickness of the electro-absorbing layer is 2 mm to 3 mm, the thickness of the magnetically absorbing layer is 2 mm to 3 mm, and the number of modified fiber sheets in the electro-absorbing and magnetically absorbing layers is 5 to 10. The minimum reflection loss range is -15.8 to -36.3 dB, preferably -22.4 dB to -36.3 dB, and more preferably ≤ -30.0 dB; the effective absorption bandwidth range is 4.9 to 12.3 GHz, preferably 7.4 dB to -12.3 dB.
[0175] Compared with Example 1, Examples 5-7 used different electrically modified microwave absorbing agents to prepare composite materials, which can all achieve effective absorption of electromagnetic waves in specific frequency bands.
[0176] The absorption performance of Examples 1-7 was compared with that of Comparative Examples 1-2, and the results are shown in Table 1 below. It can be seen that the electromagnetic synergistic absorption fiber-reinforced resin matrix composite material prepared in this invention exhibits lower minimum reflection loss and increased effective absorption bandwidth compared to materials that only undergo electrical or magnetic modification. This demonstrates that the synergy between electrical and magnetic losses can effectively improve electromagnetic absorption performance.
[0177] Table 1 Comparison of Wave Absorption Performance Test Results
[0178]
[0179]
[0180] Note: Matching thickness refers to the thickness of the measured sample.
[0181] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. An electromagnetically synergistic absorbing fiber-reinforced resin matrix composite material, characterized in that, include: Electro-absorbing wave layer, magnetic wave-absorbing wave layer; The electro-absorbing layer includes electro-modified fibers with an electro-coated modification layer on their outer periphery and a matrix resin filling the gaps between the electro-modified fibers; The magnetic wave-absorbing layer includes magnetically modified fibers with a magnetically coated modified layer on their outer periphery and a matrix resin filling the gaps between the magnetically modified fibers; The electro-absorbing layer and the magnetic absorbing layer are stacked sequentially; a modified coating layer is applied to the outer periphery of the fiber to form a regular and orderly absorbing zone, while regular and orderly refraction and reflection zones are formed in the gaps between the fibers. Due to the different materials, the absorbing zone and the refraction and reflection zone form an interface with different absorption rates. There is one electro-absorbing wave layer and one magnetic wave layer; the incident surface of the electro-absorbing wave layer is provided with a magnetic wave layer, and the incident electromagnetic wave passes through a magnetic wave layer before entering the electro-absorbing wave layer. The electro-absorbing layer comprises multiple electro-modified fiber monolayers stacked together, and the magnetic absorbing layer comprises multiple magnetically modified fiber monolayers stacked together. The minimum reflection loss of the absorbing composite material is ≤-36dB, and the effective absorption bandwidth is ≥12GHz; The electromagnetic synergistic absorbing fiber reinforced resin matrix composite material is prepared by the following method for preparing electromagnetic synergistic absorbing fiber reinforced resin matrix composite material, the method of preparing electromagnetic synergistic absorbing fiber reinforced resin matrix composite material includes: S1: Weigh out appropriate amounts of electro-modified / magnetically modified microwave absorbing agent and binder according to the proportion, and mix them thoroughly with solvent to form electro-modified microwave absorbing slurry and magnetically modified microwave absorbing slurry; S2: Electro-modified microwave absorbing paste is coated onto fiber monosheets by spraying or brushing, and then dried to obtain electro-modified fiber monosheets; magnetically modified microwave absorbing paste is coated onto fiber monosheets, and then dried to obtain magnetically modified fiber monosheets. S3: Arrange and stack the electrically modified fiber monolayers and magnetically modified fiber monolayers from step S2, and inject matrix resin to form an electromagnetic synergistic absorbing fiber reinforced resin matrix composite material. In step S1, the mass ratio of the electrically modified microwave absorbing agent to the binder in the electrically modified microwave absorbing slurry is (4~20):1; the mass ratio of the magnetically modified microwave absorbing agent to the binder in the magnetically modified microwave absorbing slurry is (30~50):1; the amount of solvent used relative to the solid component in the electrically modified microwave absorbing agent slurry and the magnetically modified microwave absorbing agent slurry is 300 ml / kg ~ 500 ml / kg; by dissolving the microwave absorbing material in a polar solvent to prepare a slurry and coating it on the outer surface of the fiber, a regularly ordered refractive and reflective zone of appropriate size is formed in the gap between the fibers.
2. The electromagnetic synergistic absorbing fiber-reinforced resin matrix composite material according to claim 1, characterized in that, The electrocoating modification layer includes an electromodified microwave absorbing agent and necessary adhesives; the magnetic coating modification layer includes a magnetically modified microwave absorbing agent and necessary adhesives.
3. The electromagnetic synergistic absorbing fiber-reinforced resin matrix composite material according to claim 2, characterized in that, The electromodified microwave absorbing agent includes one or more of the following: multi-walled carbon nanotubes, activated carbon, highly conductive carbon black, reduced graphene oxide, or vapor-grown carbon fibers.
4. The electromagnetic synergistic absorbing fiber-reinforced resin matrix composite material according to claim 3, characterized in that, The magnetically modified microwave absorbing agent includes metal oxides composed of one or more of iron, cobalt, and nickel, or alloys composed of two or more of iron, cobalt, and nickel.
5. A method for preparing an electromagnetically synergistic absorbing fiber-reinforced resin matrix composite material, characterized in that, The preparation of the electromagnetic synergistic absorbing fiber-reinforced resin matrix composite material according to any one of claims 1-4 comprises: S1: Weigh out appropriate amounts of electro-modified / magnetically modified microwave absorbing agent and binder according to the proportion, and mix them thoroughly with solvent to form electro-modified microwave absorbing slurry and magnetically modified microwave absorbing slurry; S2: Electro-modified microwave absorbing paste is coated onto fiber monosheets by spraying or brushing, and then dried to obtain electro-modified fiber monosheets; magnetically modified microwave absorbing paste is coated onto fiber monosheets, and then dried to obtain magnetically modified fiber monosheets. S3: Arrange and stack the electrically modified fiber monolayers and magnetically modified fiber monolayers from step S2, and inject matrix resin to form an electromagnetic synergistic absorbing fiber reinforced resin matrix composite material. In step S1, the mass ratio of the electrically modified microwave absorbing agent to the binder in the electrically modified microwave absorbing slurry is (4~20):1; the mass ratio of the magnetically modified microwave absorbing agent to the binder in the magnetically modified microwave absorbing slurry is (30~50):1; the amount of solvent used relative to the solid component in the electrically modified microwave absorbing agent slurry and the magnetically modified microwave absorbing agent slurry is 300 ml / kg ~ 500 ml / kg; by dissolving the microwave absorbing material in a polar solvent to prepare a slurry and coating it on the outer surface of the fiber, a regularly ordered refractive and reflective zone of appropriate size is formed in the gap between the fibers.
6. An application of an electromagnetically synergistic absorbing fiber-reinforced resin matrix composite material, characterized in that, The electromagnetic synergistic absorbing fiber reinforced resin matrix composite material according to any one of claims 1-4 or the electromagnetic synergistic absorbing fiber reinforced resin matrix composite material prepared by the preparation method of claim 5 is used for electromagnetic radiation protection and interference protection in buildings, equipment, etc.
Citation Information
Patent Citations
High-temperature-resistant broadband wave-absorbing / bearing composite material and preparation method thereof
CN113696567A